Dynamic soil-structure interaction: A three-dimensional numerical approach and its application to the Lotung case study. (October 2017) - Amorosi, A.; Boldini, D.; di Lernia, A.
Abstract: This paper presents a three-dimensional non-linear finite element (FE) approach to analyse the dynamic soil-structure interaction (SSI) phenomena observed at the Lotung Large-Scale Seismic Test (LSST) site. The numerical study is carried out in the time domain by a commercial FE code, taking into account the non-linear behaviour of soil and the multi-directional nature of real seismic events. The soil response is simulated by an isotropic hardening elasto-plastic hysteretic model (HSsmall) implemented in the material model library of the code. This model allows to describe the non-linear cyclic response ranging from small to large strain amplitudes and to account for the variation of the initial stiffness with depth. In the paper, the FE numerical approach is first validated through a series of parametric analyses simulating simplified cases (i.e. linear visco-elastic structures founded on a homogeneous linear visco-elastic soil deposit) for which analytical solutions exist. Then, it is adopted to back-analyse the behaviour of the 1/4-scale nuclear power plant containment structure constructed at the Lotung LSST site which was shook by several earthquakes of different intensities and frequency contents. The FE results are thus compared to the recorded in-situ free-field and structural motions, highlighting the satisfactory performance of the numerical model in replicating the observed response. The overall outcome of this research proves that nowadays complex dynamic SSI phenomena can be tackled by direct approach, overpassing the strong simplifications of the well-established substructure approaches.